The Use of PT Petro Kimia’s by-Product Gypsum as Fill Materials - Raditya Widiatama; Indrasurya Budisatria Mochtar; Noor Endah Mochtar (Institut Teknologi Sepuluh Nopember, 2020)
Gypsum is a by-product of the Phosphoric Acid factory PT Gresik Petrochemicals; it is produced around 1,200,000 tons/year. In order to reduce the amount, an effort needed to use gypsum as fill materials. For this purpose, the problem needs to be considered is that gypsum should not contain substances that harmful to the environment and meet the fill materials requirements. In order to answer all these questions, chemical tests were carried out to determine its heavy metal content. Gypsum plasticity and its particle size distribution were determined by conducting Atterberg limit and sieve analysis tests. Compaction test and CBR test were also carried out to determine the density and its strength. Those results were then analyzed using